HEALTH RISK ASSESSMENT DUE TO THE METALS EXPOSURE OF GROUNDWATER IN THE AREA OF SIDOARJO MUD (LUSI), EAST JAVA, INDONESIA - Adiyaksa, Ilham Putra; Savichev, Oleg G.; Martino, Antonio Di (Directorate of Research and Community Service (DRPM), 2023)
Lumpur Sidoarjo (LUSI) (Sidoarjo mud), which has its center in Porong, Sidoarjo, East Java, has had a major impact on environmental conditions, especially on water quality. Our previous analysis proves that the groundwater in this area has been contaminated, especially by heavy metals. In this case, the presence of contaminants from Fe, Mn, and Hg was detected. Heavy metals in this water will certainly affect human health if this contaminated water is consumed, considering that groundwater is the main water resource utilized by local people in this area. Thus, the objective of this study is assessment of health risk from exposure to Fe, Mn, Zn, As, and Hg in the groundwater near to LUSI. The calculation method used the formula recommended by the United States Environmental Protection Agency (US EPA). Scenario subjects for the calculation included 1) children aged 1-3 years, 2) children aged 4-8, 3) children aged 9-12, 4) career women, and 5) career men. The calculation results show that a Hazard Quotient (HQ) value of more than 1 has been detected in several samples and subjects. The highest HI value is in sample B5, and the smallest is in sample B2. In addition, the calculations show that there is a risk of cancer effects from Hg-contaminated water.